Defects in Zn1-x-yCoxMgyO nanoparticles: Probed by XRD, RAMAN and PAS techniques - Singh V.P.; Singh R.K.; Das D.; Rath C. (My University, 2025)
Wurtzite Zn1-x-yMgxCoyO nanoparticles of size 14-20 nm are synthesized by the conventional coprecipitation route and are analyzed using XRD, FESEM, UV-visible, Raman, and Positron annihilation spectroscopic techniques. XRD patterns reveal formation of a single wurtzite phase of ZnO on adding Mg, Co or both. In addition to six Raman active modes corresponding to the wurtzite structure of space group C6ν 4, we also observe additional Raman modes at 519, 544 and 673 cm -1 irrespective of the dopant type and concentration. These modes exactly match with the silent vibrational modes of ZnO lattice as calculated by the ab initio calculations. From positron life time measurements, we observe that while the shortest lifetime τ1, the lifetime of positrons that annihilate in the grain boundary regions match well with the lifetime of positrons in a defect free ZnO (τ1∼158 ps), the intermediate lifetime, τ2 of all three samples match with the life time of positron annihilating at the cluster of (Zn+O) di-vacancies. We conclude that the origin of additional Raman modes is not due to impurities as reported in the literature rather is due to host lattice defects. © 2012 Elsevier Ltd. All rights reserved.